THE SELECTION OF PROPERTY MANAGEMENT SOFTWARE - Van den Berg, S.; Cloete, C.E. (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: Property management software packages have become essential tools in the management of properties and related facilities. In this paper, criteria for the comparative evaluation of property management software packages are developed and the various software packages available in South Africa are evaluated against these criteria. Recommendations are made as to the appropriateness of the various software packages to the needs of the user. AFRIKAANSE OPSOMMING: Sagtewarepakkette vir eiendomsbestuur is